2018
DOI: 10.1299/jamdsm.2018jamdsm0129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnDTP triboflim's morphology on friction behaviors of DLC coatings: Tribofilm characterization by 3D scanning electron microscope observation

Abstract: ZnDTP antiwear additive for lubricating oil is known to absorb strongly on sliding surfaces in boundary lubricated tribosystems, forming a tribofilm, which is able to reduce the wear of involved surfaces. It is also known to increase the friction coefficient in most DLC/DLC contacts, with the exception of ta-C DLC / ta-C DLC contact, for which the difference in friction behaviors between a base oil + ZnDTP additive lubricated tribosystem and a base oil lubricated tribosystem is not very significant. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 15 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…Using a metal morphing surface to control lubricant thickness between mating surfaces so that friction force is reduced [1,2], and using a carbonaceous hard coating (for example, tetrahedral amorphous carbon (ta-C) [3][4][5][6], hydrogenated amorphous carbon (a-C:H) [7][8][9], amorphous carbon (a-C), or other dopant types [10,11]) are methods for overcoming this situation. However, some additives cause high coating wear [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Using a metal morphing surface to control lubricant thickness between mating surfaces so that friction force is reduced [1,2], and using a carbonaceous hard coating (for example, tetrahedral amorphous carbon (ta-C) [3][4][5][6], hydrogenated amorphous carbon (a-C:H) [7][8][9], amorphous carbon (a-C), or other dopant types [10,11]) are methods for overcoming this situation. However, some additives cause high coating wear [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Murashima et al revealed that nitrogen-containing ta-C coatings have lower surface energy, resulting in few adhesion between ceramic particles and the ta-C coatings [25]. The coatings are known to develop unique tribolayer derived from oil additives, providing low friction and low wear tribo lms [26][27][28][29]. The a-C:H coatings are generally deposited by chemical vapor deposition (CVD) method, showing lower hardness, carbon diffusion during friction, and less chemical stability due to its sp2-rich carbon structure [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The coatings are known to develop unique tribolayer derived from oil additives, providing low friction and low wear tribo lms [26][27][28][29]. The a-C:H coatings are generally deposited by chemical vapor deposition (CVD) method, showing lower hardness, carbon diffusion during friction, and less chemical stability due to its sp2-rich carbon structure [27][28][29][30]. The carbonaceous structure is considered to easy to react with additive molecules on the surface, developing thick tribo lm or bring severe chemical wear of the coating [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The thicknesses and morphologies of these tribofilms are affected by intrinsic parameters of the DLC coatings, i.e. hydrogen content, sp 2 / sp 3 ratio, presence of dopants, surface roughness and mechanical properties 6 , 20 . The former three factors alter chemical reactivity of DLC surfaces and thus reaction rates of ZDDP, whereas the latter two factors affect the mechanical response of the system such as contact pressure and geometry, and elastic/plastic deformation of surface asperities.…”
Section: Introductionmentioning
confidence: 99%